The Pierre Auger Observatory IV: Operation and Monitoring - Collaboration, TPA; Abreu, P; Aglietta, M; Ahn, E; Albuquerque, I; Allard, D; Allekotte, I; Allen, J; Allison, P; Castillo, J; Alvarez-Muñiz, J; Ambrosio, M; et al. (2011)
Technical reports on operations and monitoring of the Pierre Auger Observatory